Epidemiology of paediatric chronic heart failure in Germany—A population‐based analysis - Alexej Bobrowski; Sven Klebs; Marco Alibone; Leonore Bovy; Dennis Häckl; Thilo Fleck; Brigitte Stiller (ESC Heart Failure)
Abstract Aims Paediatric chronic heart failure (CHF) is associated with significant morbidity. The aim of this study was to describe paediatric CHF epidemiology in Germany. Methods and results This is a retrospective cross‐sectional analysis of anonymized healthcare claims data in the InGef database. This database includes longitudinal data from a representative sample of the German population of approximately 4.8 million insured members. We included individuals <18 years from 2016 to 2021. CHF was defined by ≥2 diagnoses in different quarters of the year as inpatient or outpatient, using ICD‐10‐GM codes I50.‐ or P29.0. The number of eligible children in the database was 674 462 in 2016 and 660 692 in 2021. Prevalence of CHF per 100 000 children was 20.6 [95% confidence interval (CI), 17.3–24.3] in 2016 and 19.4 (95% CI, 16.2 to 23.0) in 2021. Incidence per 100 000 children was 9.6 (95% CI, 7.4 to 12.3) in 2016 and 7.6 (95% CI, 5.6 to 10.0) in 2021 for newly diagnosed CHF. All‐cause hospitalizations occurred in 47.3% to 57.7% of children with CHF per year. Up to 6.3% of children with CHF were hospitalized, coded primarily for heart failure. Mortality of children with CHF was <5 death per year in the studied population. In 128 children with CHF in 2021, the most common ICD‐coded comorbidities were congenital malformations of cardiac septa (57.8%), atrial septal defect (44.5%), congenital malformations of the great arteries (43.0%) and ventricular septal defect (32.0%). Coded treatment modalities for paediatric CHF in 2021 included angiotensin‐converting enzyme inhibitors or angiotensin II type 1 receptor blockers (18.8%), beta‐blockers (17.2%), mineralocorticoid receptor antagonists (14.8%) and surgical procedures (13.3%). Conclusions This representative cohort study reveals a relatively high incidence proportion. Approximately half of the children with CHF are hospitalized annually while mortality is low.